EXPECTATIONS AND PERCEPTIONS OF SERVICE USERS TOWARDS THE SERVICE QUALITY OF LANG SUAN HOSPITAL, LANG SUAN DISTRICT CHUMPHON PROVINCE - Laobandit , Jinjuta; Phongpaew, Aniruth; Kasemwutthichai, Winai (Journal of MCU Phetchaburi Review, 2025)
The objectives of this research were 1) To study the level of expectations and perceptions of service users towards the service quality, 2) To compare the characteristics of service users with their expectations towards the service quality, 3) to compare the characteristics of service users with their perceptions towards the service quality, 4) to compare the differences in expectations and perceptions of service users towards the service quality. The sample consisted of 385 service users. The instrument employed was a questionnaire. The statistics used in data analysis represent mean, standard deviation, t-test, and one-way ANOVA. The research results revealed that 1) Expectations and perceptions of service users towards the quality of service, both overall and in each aspect, had the highest average value. The perception had an average value higher than expectations and was extremely satisfied in all aspects. 2) Service users with different genders, ages, education levels, and occupations had expectations of service users towards the quality of service. 3) Service users with different genders, ages, education levels, and occupations had different perceptions of service quality. 4) Expectations and perceptions of service users towards the quality of service were different, both overall and in each aspect. At the 0.05 statistical significance level.